PIDANA SEUMUR HIDUP DITINJAU DARI SISTEM PEMASYARAKATAN DALAM UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Putu Anandayoga, I Gede Bagus; Marhaendra Wija Atmadja, Gede (Kertha Wicara : Journal Ilmu Hukum, 2014)
Life imprisonment that was stipulated in article 12 of the penal code gave no clear explanaition about what is meant by life imprisonment and how long it would be. The absence of the clear explanation showed there is happened vagueness norm. so, how about the developing of the regulation of the life imprisonment in Indonesia today, and how it is seen form the correctional system based on act number 12 year 1995 regarding with penal law. Article 10 of criminal code that is regulating varius types of criminal is one of which, is about life imprisonment, but there is no explanation, so it causes various interpretation really the purpose of punishment in the penal law is not revenge, but to emphasized to coaching and teaching so that a punishment should have a humanity in it humanity for justice and educational.
Keywords: life imprisonment, purpose of punishment, penal law.